PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA - Rupina Magdalena Br Tarigan (JURNAL TEMATIK, 2019)
The problem in this study is that student learning outcomes have not been maximized. The purpose of this study is the effect of Make A Match Learning Model Against Student Learning Outcomes in Natural Science Subjects in Class VI SD Negeri 060937 Medan Johor. This type of research is a quasi-experimental. This research was conducted at SD Negeri 060937 Medan Johor. The population of this research is all students of Class VI of SD Negeri 060937 Medan Johor, with a total of 50 students and the study sample is divided into two parallel classes. Data collection tools used are tests and data analysis used are normality test, homogeneity test and hypothesis testing using an Independent Test between two factors. From the results of data analysis, it was found that the learning outcomes of students in the subject matter of Natural Sciences Magnet material and its properties after using the Make A Match Learning Model in Class VI SD Negeri 060937 Medan Johor, obtained an average value of 82.57 and student learning outcomes in the subjects Science of Magnet Material and Its Properties after using Conventional Learning in Class VI Medan Johor State Elementary School, obtained an average value of 76.23. Thus it can be concluded that there is an influence of the use of Make A Match Learning Model Against Student Learning Outcomes in Class VI SD Negeri 060937 Medan Johor.